2016
DOI: 10.5455/ijmsph.2016.31082015141
|View full text |Cite
|
Sign up to set email alerts
|

Study on stress among first-year medical students of Kurnool Medical College, Kurnool

Abstract: Background: Stress is an inevitable part of medical education, and lack of adequate stress-coping skills may affect the students variedly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
7
17
2
Order By: Relevance
“…1 It is a highly subjective phenomenon so that each person has different stress levels. 2 Several studies have shown that medical students experience different degrees of stress in their study period which could be attributed to problems associated with social relationships, academic difficulties, financial issues, health problems etc. 1,3 In some individuals, stress can lead to an increased performance which could be one of the measures they adopt to cop up with the stress.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a highly subjective phenomenon so that each person has different stress levels. 2 Several studies have shown that medical students experience different degrees of stress in their study period which could be attributed to problems associated with social relationships, academic difficulties, financial issues, health problems etc. 1,3 In some individuals, stress can lead to an increased performance which could be one of the measures they adopt to cop up with the stress.…”
Section: Introductionmentioning
confidence: 99%
“…Stress is characterized as mental and/or physical tension with the presence of intense feelings of worry and anxiety. Stress is associated with patients' ill responses and/or ineffective coping mechanisms towards a range of stressors, which could negatively impact their overall psychological, physical and social wellbeing (Seo et al, 2015;Fares et al, 2016;Siddiqui 2016;Sreedevi et al, 2016;Konjengbam, 2015). Chronic exposure to emotional stress which is especially exasperated in highly demanding environments could eventually lead to burnout; burnout triggers conditions such as depression, insomnia, feelings of detachment and/or fatigue, as well as excessive anxiety over future concerns (Seo et al, 2015;Fares et al, 2016;Siddiqui, 2016;Sreedevi et al, 2016;Konjengbam, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although stress is inevitable, yet burnout is preventable. Therefore, identifying stress among students early during their pre-clinical or training years would help prevent stress and/or burn, and perhaps even affect the long-term quality of their patient care (Sreedevi et al, 2016;Konjengbam, 2015). Stress and burnout are endemic in multi-medical institutions and are usually exhibited early during the preclinical stage, ranging from 62-75%; whereas stress and burnout during the clinical stage range from 25.6-78% and 10-45%, depending on the instrument used for diagnosis (Galan et al, 2014;Youssef, 2016;Ishak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An intervention was planned in two sessions, and students were educated on how to handle stress by audio visual aids, personal interviews and group discussions. 14 Thangaraj et al study done in Bangalore medical college showed that the age group was 17-20 years and the mean age was 18.16. 15 In present study maximum number of students 73 (49%) are under stress.…”
Section: Discussionmentioning
confidence: 99%
“…13 Various stress factors reported in studies among medical students are academic related such as exams, getting poor marks, inability to cope, helplessness, increased psychological pressure, mental tension and too much work load. 14 The transition from pre-clinical to clinical training has also been identified as a crucial stage of medical school regarding student stress. This study therefore has been planned to identify the prevalence of stress and possible factors responsible for it among first year medical students.…”
Section: Introductionmentioning
confidence: 99%